2011
DOI: 10.1111/j.1365-2141.2011.08580.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163 levels in children with sickle cell disease

Abstract: Summary Sickle cell disease (SCD) is characterized by vasculopathy, which has been causally linked to intravascular haemolysis and high levels of free plasma haemoglobin. Soluble CD163 (sCD163) is implicated in the clearance of free plasma haemoglobin and high plasma concentrations have been linked to arterial disease. We therefore investigated the value of sCD163 as a biomarker in children with SCD, and also measured haptoglobin levels in this population. We measured sCD163 in 25 control children with no haem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…In another study, although the studied number of SCD patients with acute pain was too small to allow statistical analysis, yet, acute pain was associated with increased sCD163 levels [21]. Our findings further confirmed these results.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In another study, although the studied number of SCD patients with acute pain was too small to allow statistical analysis, yet, acute pain was associated with increased sCD163 levels [21]. Our findings further confirmed these results.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, Moller et al [21] reported that hydroxyurea therapy significantly reduced sCD163 concentrations Soluble CD163 in SCD and SCT Tantawy et al 645 with parallel increase in HbF in SCD. The inverse relationship between sCD163 and HbF demonstrated in the current work further elucidated these results.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[6] Thus, it is a macrophage-specific marker in patients with disorders of inappropriate macrophage activation. [7] Its values may be elevated in conditions as wide ranging as coronary atherosclerosis,[8] Gaucher's disease,[910] myeloid leukemia,[10] idiopathic arthritis,[11] and sickle cell anemia[12] to bacteremia. [13] Investigators have emphasized the potential role of sCD163 as a diagnostic parameter in hematological and inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%